Implementation And Optimization Strategies for Handling School Dropouts - Kurniati Kurniati; Mujahid Yunus; Abdul Samad Arief (Journal La Sociale, 2026)
Data from the Makassar City Education Office in 2022 reported approximately 17,000 school dropouts. This phenomenon largely stems from low-income families, where children worked to support household finances. The high dropout rate has contributed to increasing unemployment and the declining competitiveness of human resources. In addition, school dropouts were more vulnerable to various social problems such as violence, crime, and child exploitation. This study aimed to analyze the implementation strategies for addressing school dropouts in Makassar City, including the supporting and inhibiting factors. This is a qualitative study with a case study approach in Education Office of Makassar during January–March 2025. Data were collected through in-depth interviews with nine informants, observations, and document analysis. The study found that dropout management strategies have been carried out through cross-sectoral collaboration involving the government, private sector, and community stakeholders. However, heavy workloads and limited institutional support remain major challenges. Optimization efforts included the implementation of equivalency programs for reintegration into formal schools, strengthening an integrated database system, multi-stakeholder approaches, and the provision of flexible alternative education. This study recommends simplifying procedures, establishing regular cross-sectoral coordination forums, and conducting periodic evaluations of resource allocation to ensure the effectiveness of school dropout management programs.